2004
DOI: 10.1073/pnas.0308111101
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of a Δ12 fatty acid desaturase gene from spinach in transgenic pigs

Abstract: Linoleic acid (18:2n-6) and ␣-linolenic acid (18:3n-3) are polyunsaturated fatty acids that are essential for mammalian nutrition, because mammals lack the desaturases required for synthesis of ⌬12 (n-6) and n-3 fatty acids. Many plants can synthesize these fatty acids and, therefore, to examine the effects of a plant desaturase in mammals, we generated transgenic pigs that carried the fatty acid desaturation 2 gene for a ⌬12 fatty acid desaturase from spinach. Levels of linoleic acid (18:2n-6) in adipocytes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(79 citation statements)
references
References 44 publications
(45 reference statements)
0
76
0
3
Order By: Relevance
“…The transgenesis significantly affected the fatty-acid composition of lipids in tissues of modified pigs, that is the white adipose tissue of transgenic pigs contained 20% more LA in comparison with wild pigs. As stressed by the authors, the results of their study demonstrated the functional expression of a plant gene for a fatty-acid desaturase in mammals, opening prospects of modifying the lipid composition of animal-origin products using transgenic technology (Saeki et al, 2004). Since the authors produced four transgenic pigs of the third generation farrowed by a transgenic female, and all of them grew to a fertile age, their results indicated that it is a possibility to transferring desaturase transgene to subsequent generations.…”
Section: Modifications Of the Composition Of Meat Lipidsmentioning
confidence: 96%
See 1 more Smart Citation
“…The transgenesis significantly affected the fatty-acid composition of lipids in tissues of modified pigs, that is the white adipose tissue of transgenic pigs contained 20% more LA in comparison with wild pigs. As stressed by the authors, the results of their study demonstrated the functional expression of a plant gene for a fatty-acid desaturase in mammals, opening prospects of modifying the lipid composition of animal-origin products using transgenic technology (Saeki et al, 2004). Since the authors produced four transgenic pigs of the third generation farrowed by a transgenic female, and all of them grew to a fertile age, their results indicated that it is a possibility to transferring desaturase transgene to subsequent generations.…”
Section: Modifications Of the Composition Of Meat Lipidsmentioning
confidence: 96%
“…One of the first of this kind of experiment is a spectacular example of transgenesis in which a plant transgene was introduced into the genome of a mammal. Thus, Saeki et al (2004) generated, through microinjection of foreign (plant) DNA to the pronuclei of zygotes, transgenic pigs that expressed the Δ12 fatty-acid desaturase gene (fad-2) from spinach (Spinacia oleracea). This enzyme is necessary for the synthesis of LA (C18:2 n-6) and ALA (C18:3 n-3), which are necessary for normal growth and development.…”
Section: Modifications Of the Composition Of Meat Lipidsmentioning
confidence: 99%
“…The application of transgenic technology offers a powerful tool to rapidly improve agriculture production by developing domestic animals that express desired traits via genome manipulation strategies. Previous studies have demonstrated the practical application of transgenesis to improve numerous agricultural traits of domestic animals, including increased growth rate (Pursel et al, 1999), increased meat quality (Saeki et al, 2004), enhanced disease resistance (Lo et al, 1991;Clements et al, 1994), and better milk production and composition (Wheeler et al, 2001;Reh et al, 2004). Nevertheless, utilization of the cell-based method of transgenesis via SCNT has also been successfully used to alter characteristics of pork quality (Lai et al, 2006), enhance disease resistance (Denning et al, 2001a;Wall et al, 2005;Richt et al, 2007) and improve milk composition (Brophy et al, 2003).…”
Section: Improved Animal Agriculture Productionmentioning
confidence: 99%
“…This is the case for pigs expressing a desaturate gene from spinach which enhances the proportion of now saturated lipids [41].…”
Section: The Applications and The Future Of Animal Transgenesismentioning
confidence: 99%